Stroboscopy evaluation of vocal folds lesions with pre and post phono surgery - Ahmed Mohamed Eldemerdash; Essam Abd Elwanees Behiery; Asmaa El-Dessouky Rashad; Mohamed Elshahat Abdoh Elghazali; Ashraf Ali Eldemerdash (The Egyptian Journal of Otolaryngology)
Abstract Background Video laryngostroboscopy (VLS) is the most used method to visualize vocal fold vibration and mucosal wave assessment. It is used to evaluate the pliability of the vocal fold mucosa and is an indication of the health and function of the mucosal tissue and deeper layers. The aim of this work was to study the role of VLS in the evaluation of vocal fold lesions for deciding the best management plan and achieving the best post-operative voice results. Methods This prospective observational study was carried out on 70 patients aged more than 12 years, both sexes, with vocal fold (VF) lesions namely benign vocal fold lesions. Minimal associated pathological lesions (MAPLS) include VF nodules, VF polyps, and VF cysts. Results There was no significant difference between the micro flap, excision, and truncation technique regarding any of the post-procedure VLS assessments of the patients with bilateral VF nodules and unilateral VF polyp (p > 0.05). There was no significant difference between the micro flap technique, excision technique, or marsupialization technique regarding any of the Post-procedure VLS assessments of the patients with unilateral VF cysts (p > 0.05). Conclusions VLS provides a better guide for the phono surgeon to delineate the plane of dissection micro laryngeal surgery (MLS) which helps him in preserving the functional mucosa of the VF. This helps in achieving good voice quality and outcome after surgery. No significant difference between different surgical techniques used for their excision.